Syntheses and Biological Properties of Pyrido[3, 4‐b]homotropane (PHT) and its Analogues with Bridged Aza‐[n.2.1] Skeletons. Issue 8 (23rd July 2019) - Sun, Bingxia; Wang, Zhongwen
Abstract: The nicotinic acetylcholine receptor (nAChR) is one of the targets for developing drugs for the treatment of central nervous system (CNS) disorders and for control of agricultural pests. Pyrido[3, 4‐ b ] homotropane (PHT) was originally designed and synthesized by Kanne and co‐workers and showed strong affinity binding to nAChR. PHT has a novel aza‐[4.2.1]nonane skeleton. Owing to its excellent biological activities and novel chemical structure, synthetic and medicinal chemists have been attracted by this molecule. Some PHT analogues with bridged aza‐[n.2.1] skeletons were also designed and synthesized via different strategies. Herein, we summarize the syntheses of PHT and its analogues. Their biological activity study is also briefly discussed. Abstract : Hit the bull's eye ! Pyrido[3, 4‐ b ]homotropane (PHT) and its analogues have been proven to be potential synthetic nicotinic acetylcholine receptor (nAChR) ligands with bridged aza‐[n.2.1] skeletons. This Minireview gives a brief summary of the recent progress in the syntheses of PHT and its analogues, as well as their biological activity study.